New evidence for nucleolar dominance in hybrids of Drosophila arizonae and Drosophila mulleri - Oliveira, C. I. [UNESP]; Bicudo, H. E M C [UNESP]; Itoyama, M. M. [UNESP] (My University, 2006)
Drosophila mulleri (MU) and D. arizonae (AR) are cryptic species of the mulleri complex, mulleri subgroup, repleta group. Earlier cytogenetic studies revealed that these species have different regulatory mechanisms of nucleolar organizing activity. In these species, nucleolar organizing regions are found in both the X chromosome and the microchromosome. In the salivary glands of hybrids between MU females and AR males, there is an interspecific dominance of the regulatory system of the D. arizonae nucleolar organizer involving, in males, amplification and activation of the nucleolar organizer from the microchromosome. The authors who reported these findings obtained hybrids only in that cross-direction. More recently, hybrids in the opposite direction, i.e., between MU males and AR females, have been obtained. The purpose of the present study was to evaluate, in these hybrids, the association of the nucleoli with the chromosomes inherited from parental species in order to cytogenetically confirm the dominance patterns previously described. Our results support the proposed dominance of the AR nucleolar organizer activity over that of MU, regardless of cross-direction. ©FUNPEC-RP.
Keywords: Drosophila; Microchromosome; Nucleolar dominance; Nucleolus; Polytene chromosome; animal cell; animal experiment; autosomal dominant inheritance; chromosome analysis; chromosome NOR; controlled study; cytogenetics; dominant inheritance; Drosophila arizonae; Drosophila mulleri; female; gene activation; gene amplification; genetic association; hybrid; male; microchromosome; nonhuman; nucleolus; polytene chromosome; regulatory mechanism; salivary gland; X chromosome; Animals; Cell Nucleolus; Crosses, Genetic; Female; Genetic Variation; Hybridization, Genetic; Inheritance Patterns; Male; Nucleolus Organizer Region; X Chromosome; mulleri subgroup; repleta group